The College Reading Teacher's Role in Higher Education Today - Buchanan, Barbara M.; Sherman, Debora C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Adult learners--the growing clientele of higher education--require more diverse instructional models than do younger students. The adult learner may be at different developmental stages and display different learning styles, depending on the context in which the instructional interaction takes place and the attitudes, behaviors, and resources that the learner brings to that specific situation. Adults do not learn in a rigidly fixed continuum, nor do their skills develop in a predictable hierarchy. To meet the needs of these students, the new role of the college reading teacher should be that of the "college communications and learning skills professional." By working with faculty across the college, the reading teacher can promote the development of programs suited to the needs of adults and can insure a high number of students who graduate with a positive sense of themselves and their capabilities. As the focus and the role within the institution change, so changes the reading teacher's relationship to students. Today the reading teacher should act as a facilitator of students, thus more closely approximating the role of the consultant in business than the teacher in the classroom by providing resources for student self-assessment. In this new capacity, the college reading teacher becomes the agent of empowerment for students and faculty in their own institutions, for the workplace, and for the community. (HOD)
ERIC Note: Paper presented at the Annual Meeting of the European Conference on Reading (2nd, Joensuu, Finland, August 2-5, 1981).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Strategies; Content Area Reading; Educational Change; Higher Education; Integrated Curriculum; Nontraditional Students; Reading Instruction; Reading Teachers; Student Needs; Teacher Role; Opinion Papers; Speeches/Meeting Papers